Application of ionic liquids as mobile phase additives and surface-bonded stationary phase in liquid chromatography - Han, Dandan; Tian, Minglei; Park, Dong Wha; Choi, Dae Ki; Row, Kyung Ho (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2009)
Ionic liquids (ILs) have gained wide recognition as novel solvents in chemistry. Their application in analytical chemistry, especially in separating analytes, is warranted due to their unique properties such as negligible vapor pressure, good thermal stability, tunable viscosity and miscibility with water and organic solvents, as well as good extractability for various organic compounds and metal ions. Recently, some new chromatographic separation media, formed by combining ILs on silica and polymer surface using covalently or non-covalently interaction, have been developed and applied to biological separation and environment analysis. This review will focus on some of the properties of ILs and their potential application as mobile phase modifier and surface-bonded stationary phase in high-performance liquid chromatography (HPLC) separation.
Keywords: BACKGROUND ELECTROLYTE; SEPARATION; RETENTION; EPHEDRINES; ELUENT; ANTHRAQUINONES; MODIFIER; BEHAVIOR; ISOMERS; ACID